2023
DOI: 10.3390/vetsci10090544
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Passive Immunity Transfer Is Not a Risk Factor for Omphalitis in Beef Calves

Florent Perrot,
Aurélien Joulié,
Vincent Herry
et al.

Abstract: Omphalitis is the third most frequent disease in newborn calves after neonatal diarrhea and bovine respiratory disease (BRD), but limited data on the prevalence and risk factors are available in the literature. Failure of passive immunity transfer (FPIT) is recognized as a major risk factor for diseases and mortality in calves. However, the association between omphalitis and FPIT remains poorly described. To assess this association, 964 suckler beef calves from 22 farms were included in a longitudinal cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The calf was not born in dystocia, had a well-maintained and hygienic maternity pen, and did not spend much time in the cow-calf barn due to artificial lactation. Although FPT was considered to cause omphalitis, recent studies have reported that FPT does not cause omphalitis ( 14 ). However, the occurrence of omphalitis in a calf with FPT, as in the current case, is believed to increase septicemia through hematogenous transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calf was not born in dystocia, had a well-maintained and hygienic maternity pen, and did not spend much time in the cow-calf barn due to artificial lactation. Although FPT was considered to cause omphalitis, recent studies have reported that FPT does not cause omphalitis ( 14 ). However, the occurrence of omphalitis in a calf with FPT, as in the current case, is believed to increase septicemia through hematogenous transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Omphalitis is the third most common disease in newborn calves following neonatal diarrhea and bovine respiratory disease (BRD). Nevertheless, the available information regarding this condition in cattle is limited ( 14 ). We herein report a case of omphalitis caused by T. pyogenes , with subsequent pneumonia, arthritis, and liver abscess, in a Korean native calf, as well as present appropriate guidelines for its treatment.…”
Section: Introductionmentioning
confidence: 99%